Middle class values in India and Western Europe - Ahmad,Imtiaz & Reifeld,Helmut (Editor) (Social Science Press : Distributed by D.K. Publishers and Distributors, 2001)
Contributed papers presented at a workshop held on March 7-10, 2001.